Determination of Influencer Marketing and Endorsement Strategies in Encouraging Customer Loyalty - Reni Silviah (Dinasti Publisher, 2023)
Determination of influencer marketing and endorsement strategies in driving customer loyalty is a scientific article with the aim of analyzing whether influencer marketing and endorsement have an effect on increasing customer loyalty. The literature review method or literature review, which is a systematic approach to identifying, evaluating, and analyzing previous research results that are relevant to the topic being studied. The results of this article are: 1) Influencer marketing has an effect on driving customer loyalty, 2) Endorsement has an effect on driving customer loyalty. Apart from these 2 exogenous variables that affect the endogenous variable of customer loyalty, there are still many other factors including product quality, promotion, celebrity, trust.